THE ORGANIC PRODUCTION OF CEREALS IN THE E.U. COUNTRIES AND THE PROFITABILITY OF WINTER WHEAT AND WINTER RYE IN ORGANIC FARMS IN POLAND - Marcin ŻEKAŁO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The organic production of cereals is a one of main agricultural activity in organic farms in the European Union. That production is very difficult and requires a lot of producers experience and effort. Most of all, the organic production of cereals should meet the environmental goals, but also the economic goals of producers. The first aim of the study was to explore the condition of cereals organically produced in EU countries. Secondly, the profitability of winter wheat and winter rye production in organic farms was examined, based on accountancy data of Polish FADN and Agrokoszty system. Despite the weaker production results, the organic farms in Poland may be competitive with conventional farms (at the similar production level i.e. the cereal’s growing area) due to lower direct costs incurred on the production and significant support by subsidies received.